Factors Affecting The Short Term Outcome Of Pyeloplasty In Congenital Primary Unilateral Pelvi- Ureteric Junction Obstruction In Infants and Toddlers: A Single Center trial - Mostafa Sheba; Walid Ghoneima; Mohamed El Ghoneimy; Amr Mostafa; Ahmed Salem (Pediatric Sciences Journal)
Background: Congenital ureteropelvic junction obstruction (UPJO) is by far the most common cause of pediatric hydronephrosis. UPJO standard surgical treatment is open dismembered pyeloplasty (Andersons-Hyens). Aim of the work: To study the morphological and functional outcome of dismembered pyeloplasty in infants and toddlers with unilateral UPJO. Materials and Methods: This prospective study was carried on 50 infants and toddlers aged 2 months - 36 months with unilateral UPJO at Cairo University Children Hospital. Results: The mean age of studied group was 11 ± 3 months. The main symptom was recurrent urinary tract infect in 18 (36%) of cases, followed by loin pain in 12 (24%), hematuria in 4(8%) and 16 (32%). Initial pre-operative ultrasound demonstrated moderate and severe hydronephrosis (HN) in 29 (58%) and 21 (42%) of the cases, mean cortical thickness was 6.78 ± 1.57 cm and mean anteroposterior (AP) diameter was 3.27± 0.58 cm. After 3 and 6 months, 24(48%) and 30 (60%) had mild degree of HN, 23 (46%) and 17 (34%) had moderate HN and 3 (6%) and 3 (6%) had severe HN respectively (p=0.000). The mean cortical thickness increased to 8.66 ± 1.49 mm (p=0.000). The mean AP dropped substantially as well to 2.7± 0.57 cm (p=0.000). Operative time did not influence outcome (p=0.653), yet pre-operative lesser degree of HN, more cortical thickness and lesser AP diameter was associated with better outcome (p=0.000, p=0.000 and p=0.000 respectively). Those with younger age at presentation had better outcome (p=0.001) Conclusion: The better outcome of dismembered pyeloplasty (Andersons-Hyens) relies on early diagnosis and implementation before development of HN, cortical thickness erosion and increase in AP diameter. Pyeloplasty for unilateral UPJO in younger age seems to allow cortical remodeling and regeneration. Long term follow up remains crucial to verify the long term outcome.